Bulk Nanocrystalline Thermoelectrics Based on Bi-Sb-Te Solid Solution - Bulat, L.P.; Pshenai-Severin, D.A.; Karatayev, V.V.; Osvenskii, V.B.; Parkhomenko, Yu.N.; Lavrentev, M.; Sorokin, A.; Blank, V.D.; Pivovarov, G.I.; Bublik, V.T.; Tabachkova, N.Yu. (IntechOpen, 2012)
None